METODE MENGAJAR BERVARIASI UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA - Apriyanti Apriyanti (Hipotenusa Journal of Research Mathematics Education (HJRME), 2020)
Various problems in the world of education still require concerted thinking efforts; one of these problems is in the field of mathematics studies in schools. This may be due to the way the lesson is delivered that is less effective, for that a teacher can create an interesting learning atmosphere so that it is not boring. A teacher must be able to choose a teaching system that is in accordance with the program of teaching and learning activities. In this study the method used is descriptive quantitative method, data analysis using statistical formulas. To find out student learning outcomes, the writer conducted an essay test. Based on the results obtained, it can be concluded that: "The average mathematics learning outcomes of students who are taught using varied teaching methods are more than the average mathematics learning outcomes of students who are not taught using varied teaching methods". Thus, it can be said that the application of various teaching methods has a positive effect or can improve mathematics learning outcomes.